Evaluation of the integration of the Wind-Induced Flutter Energy Harvester (WIFEH) into the built environment: experimental and numerical analysis - Aquino, Angelo I.; Calautit, John Kaiser; Hughes, Ben Richard (Elsevier, 2017)
With the ubiquity of low-powered technologies and devices in the urban environment operating in every area of human activity, the development and integration of a low-energy harvester suitable for smart cities applications is indispensable. The multitude of low-energy applications extend from wireless sensors, data loggers, transmitters and other small-scale electronics. These devices function in the microWatt-milliWatt power range and will play a significant role in the future of smart cities providing power for extended operation with little or no battery dependence. This study thus aims to investigate the potential built environment integration and energy harvesting capabilities of the Wind-Induced Flutter Energy Harvester (WIFEH) – a microgenerator aimed to provide energy for low-powered applications. Low-energy harvesters such as the WIFEH are suitable for integration with wireless sensors and other small-scale electronic devices; however, there is a lack in study on this type of technology’s building integration capabilities. Hence, there is a need for investigating its potential and optimal installation conditions.